Assessment of Microplastic and Organophosphate Pesticides Contamination in Fiddler Crabs from a Ramsar Site in the Estuary of Guayas River, Ecuador. - Villegas, Lipsi (2021)
We assessed the concentration of organophosphate pesticides (OPs) and microplastics (MPs) in water and sediments from the burrows, and tissues of the fiddler crabs Leptuca festae and Minuca ecuadoriensis, from Isla Santay, a Ramsar site in the estuary of the Guayas River, Ecuador. MPs concentrations in the burrows were 660 ± 174.36 items kg−1 (w.w.) and 26 ± 1 items L−1 in collected sediments and water, respectively. Regarding OPs, water and sediment concentrations were up to 26 times above the USEPA thresholds for chronic exposure, indicating environmental risk. MPs were found in tissues collected from both species. The highest abundance was in the gills followed by the digestive tract and hepatopancreas. OPs concentrations in tissues were below the detection limits. Because fiddler crabs are chronically exposed to environmental contamination, they are suitable bioindicators to monitor Isla Santay and to comprehend human impacts in coastal environments of Ecuador.